PENGARUH PEMBERIAN KREDIT USAHA RAKYAT (KUR) PT BANK RAKYAT INDONESIA,TBK (PERSERO) UNIT PALAKKA TERHADAP PENINGKATAN PENDAPATAN EKONOMI USAHA MIKRO KECIL (UMK) DI KOTA WATAMPONE - Marniati Syam; Ria Musfira (Islamic Banking and Finance, 2021)
ABSTRACTThis study aims to determine the positive and significant effect of People's Business Credit (KUR) of PT Bank BRI Palakka Unit on increasing the income of Micro and Small Enterprises (UMK) in Watampone City. The population in this study were all customers who borrowed People's Business Credit (KUR) from PT Bank BRI Palakka Unit. Determination of the number of samples using the Slovin technique of 66 samples. Data were analyzed using simple regression. The results of the study concluded that People's Business Credit (KUR) had a positive and significant effect on increasing Micro and Small Business Income (UMK) in Watampone City. Based on the research findings, in this study the capital factor makes a major contribution in increasing business income, so it is hoped that related parties will facilitate capital for business actors.